Naval Health Research Center Surveillance for Meningococcal Disease. (21st March 2019) - Broderick, Michael; Myers, Christopher
Abstract: Historically, meningococcal disease has had a devastating impact on U.S. military personnel, but since the introduction of a vaccine in the 1970s, rates have dropped over 90%. 1 Department of Defense instructions mandate a meningococcal vaccine for all service personnel. In the last 5 years, rates of meningococcal disease in the military are similar to the U.S. general population. The active duty incidence was 0.21 cases per 100, 000 person-years from 2013–2017. Six cases occurred in the 6 months between September 2016 and February 2017; of these, only one was determined to be a vaccine-covered strain. Ongoing surveillance shows vaccination has resulted in a dramatic reduction in meningococcal cases in the military; however, it also demonstrates cases continue to occur sporadically. The recent emergence of new cases reminds us that surveillance and accompanying research are important for evaluating changes in the disease and informing new vaccine development and policy.